Religious ambiguity, diversity, and rationality (2017)
The article explores the relation between the propositional and non-propositional dimensions of religious belief in order to show that the latter guides the process of justification and represents its limit. It argues that the non-propositional dimension also has cognitive value because it constitutes a sort of pre-Theoretical epistemic election that does not pertain exclusively to religious faith. The article also delves into the notion of religious ambiguity, both in its intellectual and experiential in-Terpretations, and argues that the relationship between the propositional and the non-propositional dimensions of faith is mediated by the guiding role of the metaphysical presuppositions established by religious experience.